Kajian Terhadap Perikatan Alamiah MenurutKitab Undang–Undang Hukum Perdata (KUH Perdata) - Bing Waluyo (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2021)
The source of the engagement as regulated in Article 1233 of the Civil Code, can occur due to two things, namelyan engagement born of an agreement and an engagement born of law. Engagements born from laws consist ofengagements born from laws only and those born from laws due to human actions which can be distinguishedinto human actions that are in accordance with the law (rechtmatige) and those that are against the law(onrechtmatige). Engagements born from the law due to human actions in accordance with the law, one ofwhich is contained in Article 1359 of the Civil Code, which consists of two paragraphs, namely paragraph 1which regulates the right to claim back payments that are not owed, and paragraph 2 regulates if a personlegally voluntarily fulfill the obligations of the natural engagement, then the payment is not a payment that isnot owed, it can be concluded from the contents of the article, namely that the payment made by the debtorcannot be requested back. Furthermore, regarding how and what is meant by natural engagement, the CivilCode does not explain in detail, on this basis it encourages the author to write a study on natural engagementaccording to the Civil Code (KUH Perdata). The approach method in this paper is normative juridical, while thespecifications in this paper are descriptive analytical.